The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/mi.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

TLR1-induced chemokine production is critical for mucosal immunity against Yersinia enterocolitica

Abstract: Our gastrointestinal tract is a portal of entry for a number of bacteria and viruses. Thus this tissue must develop ways to induce antigen-specific T cell and antibody responses quickly. Intestinal epithelial cells are a central player in barrier function but also in communicating signals from invading pathogens to the underlying immune tissue. Here we demonstrate that activation of TLR1 in the epithelium leads to the up-regulation of the chemokine CCL20 during oral infection with Yersinia enterocolitica. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
(76 reference statements)
1
31
0
Order By: Relevance
“…Secreted IgA is essential for optimal mucosal defense, since it is able to inhibit mucosal colonization and invasion by pathogenic microorganisms [40]. The IgA response seems to be important for protecting the intestinal mucosa against infection with Y. enterocolitica [41]. Although, in our study, the specific IgA response to Y. enterocolitica was not measured, our data demonstrate an adjuvant effect of C4 on the production of secreted IgA in infected mice.…”
Section: Discussionmentioning
confidence: 60%
“…Secreted IgA is essential for optimal mucosal defense, since it is able to inhibit mucosal colonization and invasion by pathogenic microorganisms [40]. The IgA response seems to be important for protecting the intestinal mucosa against infection with Y. enterocolitica [41]. Although, in our study, the specific IgA response to Y. enterocolitica was not measured, our data demonstrate an adjuvant effect of C4 on the production of secreted IgA in infected mice.…”
Section: Discussionmentioning
confidence: 60%
“…Th17 is known to have a protective immune response against bacteria in the gut, and the TLR1/2 signal in dendritic cells contribute to the Th17 polarization at mucosal surface by inducing interleukin-6 (IL-6) and IL-23 (15). However, there is still controversy over whether Th17 has a tumor-promoting function or has a tumor-suppressing function in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that TLR1 signaling is critical for mucosal protection against oral infection caused by the gram-negative pathogen Yersinia enterocolitica (DePaolo et al, 2012; Sugiura et al, 2013). Ingestion of Y. enterocolitica in contaminated food and water causes a self-limiting gastroenteritis characterized by colonization of the distal ileum and translocation to the Peyer’s patch and mesenteric lymph nodes (Trulzsch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%